Testing the accruals anomaly based on the speed of price adjustment - Choy, Siu Kai; Lobo, Gerald J; Tan, Yongxian (Routledge, 2021)
In this study, we investigate the nature of the accruals anomaly by analyzing the speed of price adjustment to accruals information. Consistent with the mispricing hypothesis, we find that a relatively larger proportion of accruals premium is distributed near the filing dates among low limits-to-arbitrage stocks and during periods of increased arbitrage activity. We also discuss our findings in the context of q-theory.